Assessment of industry 4.0 competencies and improvement opportunity perceived by lecturers of Azman Hashim International Business School - Mohamad Fawzy Bakry, 1997-, author; Tan, Owee Kowang, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2020